Escape from the land of snows : the young Dalai Lama's harrowing flight to freedom and the making of a spiritual hero - Talty, Stephan (Crown Publishers, 2010)
Documents the Dalai Lama's flight from Tibet to India in 1959, describing the violent uprising in Lhasa between Tibetan rebels and Chinese occupiers and the near-death incidents that the Buddhist spiritual leader endured.